Efficacy and safety of stereotactic radiotherapy on elderly patients with stage I-II central non-small cell lung cancer - Ji, Xiaoqin; Zhou, Bin; Huang, Hua; Wang, Yong; Jiang, Wanrong; Wang, Jiasheng; Ding, Wei; Wang, Zhen; Chen, Guanha; Sun, Xiangdong (Frontiers in Oncology, 2024)
Background: Many studies demonstrated the safety and efficacy of SBRT in the treatment of elderly patients with early-stage non-small cell lung cancer (NSCLC). However, those studies focused on patients with peripheral lung cancer. This study aimed to evaluate the clinical efficacy and toxicity of SBRT in elderly patients with stage I-II central NSCLC in single institution.Methods: From April 2009 to January 2020, a retrospective study was conducted on patients ≥ 65 years old with stage I-II NSCLC that was centrally localized and treated with SBRT at a single institution. Absolute C-reactive protein (CRP)/albumin ratio (CAR) and body mass index (BMI) recorded at pretreatment were analyzed. Endpoints included overall survival (OS), progression-free survival (PFS), cancer-specific death, noncancer-specific death, local progression (LP) and distant progression (DP).Results: Stereotactic body radiation treatment (SBRT) was administered to a total of 44 patients.The most common dose fractionation schedule was 60 Gy given in 5 fractions. The median PFS of the cohort was 31 months (95% CI, 19.47-42.53 months). The median OS of all patients was 69 months (95% CI, 33.8-104.2 months). The median time to noncancer-specific death was 54.5 months. The median time to cancer-specific death was 36 months. The cumulative incidences of cancer-specific death at 1 year, 5 years, and 10 years were 11.63% (95%CI, 4.2-23.23%), 42.99% (95%CI, 27.56-57.53%), and 65.94% (95%CI, 45.76-80.1%), respectively. pre-SBRT BMI of ≤ 22.77 (HR 4.60, P=0.001) and pre-SBRT CAR of ≤0.91 (HR 5.19, 95% CI 2.15-12.52, P＜0.000) were significant predictors of higher OS on multivariable analysis. The median times to LP and DP were 10 months and 11 months, respectively. In terms of acute toxicity, grade 1 including cough (38.64%), radiation pneumonitis (29.55%), anemia (25%), and fatigue (20.45%) was often observed. There was no evidence of grade 4 or 5 acute toxicity. In terms of late toxicity, 2 patients developed grade 1 pulmonary fibrosis during follow-up.This study showed that SBRT can effectively control local tumor progression, and have acceptable toxicity for elderly patients with centrally located stage I-II NSCLC. Lower pre-SBRT BMI and lower pre-SBRT CAR were associated with a decreased risk of cancer-specific death.